Properties of three layered hybrid particleboard from sawdust and Acacia Mangium - Ismail, Bukhari; Mohd Noor, Mohd Nazrin; Wan Ibrahim, Wan Muhammad Hilmi (2012)
Effects of different densities on the properties of hybrid wood sawdust-Acacia Mangium composites were investigated in this study. Three layered hybrid composites from sawdust and Acacia Mangium were fabricated with 10: 10: 10 resin content within face/back (sawdust) and core (Acacia Mangium particles) with 500, 600 and 700 kg/m3 board densities. Urea Formaldehyde (UF) was used as a binder with addition of wax. The properties of bending strength (MOR & MOE), internal bonding strength (IB), thickness swelling (TS) and water absorption (WA) were evaluated base on European Standard EN 312:2003. Result obtained indicated that bending and internal bonding strength of panel with 700 kg/m3 density was better compared with 500 and 600 kg/m3 . In conclusion, when the density of the panel increased, the mechanical properties may improve.